KEWENANGAN PERADILAN AGAMA TERHADAP SENGKETA EKONOMI SYARIAH - Zaida, Yusna (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2007)
A an lslDmic coun in lndonesi4 the Religion Coun has an authority for those. siror religion are klam or those who admit thcir obdience to Islamic laws. lla!.d on I-aw no. 3 / 2006, thero is a new authodty for this instjtution, that is to s.lvc drc dispute on syaria economy or dispute in syaria economic taw. Syaia ccoronl( is lhe Indonesian economc law which is based on svaria. Whreas r.1,,nes,an Economic law is atl rutes and taw decision which sp;ificaly arra.nge rhc ccononric acliviries. The potential eme.ging of dispute in syada economy is relarcd with contract (agreement) in syaria economy thst has familia. term akad, or dispulc of interests between lulancial iNtttution and the filnd usen- or can ,.,r" rr he. J.r .e ol rhe drfferenr perceplion or i4lerprelaliun abour rle obligaLiotr ard the righrs rhai must be fulfilled. The Religion Court as the appointed nslirution in solving the dispute on syaria business (econorny) is the right and wisc choice. This is in order to achieve the hannonv btween material laws ,.ih r, bas{d on Llarnic prir,ciples wirh rhe religio; coun insrirurjon *hjch refresents the Islamic court institution, and also to adjust with the officials who nra cr the lslamic laws.